Versatile nanocarrier based on functionalized mesoporous silica nanoparticles to codeliver osteogenic gene and drug for enhanced osteodifferentiation. - Zhou, X.; Zhang, Q.; Chen, L.; Nie, W.; Wang, W.; Wang, H.; He, C.
To achieve enhanced stimulatory effects on the osteogenic differentiation of stem cells, the combination of dual factors with synergistic bioactivity has been regarded as the most effective and powerful strategy. In this study, polylysine-modified polyethylenimine (PEI-PLL)copolymers with various molecular weight PEI blocks were first synthesized and evaluated focusing on their cytotoxicity and gene transfection efficiency, and the results demonstrated that the synthesized copolymer PEI-PLL-25k (synthesized using 25 kDa PEI)exhibited lower cytotoxicity and higher in vitro transfection efficiency than commercial PEI-25k (Mw = 25 kDa). In order to effectively load and deliver plasmid DNA and osteogenic drug dexamethasone (DEX), PEI-PLL-25k copolymer and arginine-glycine-aspartate (RGD)peptide were successively anchored onto the surface of mesoporous silica nanoparticles (MSNs)to construct the dual-factor delivery system, which allows the surface adsorption of DNA and DEX loading in the mesopores of MSNs. The modification of PEI-PLL-25k copolymer and RGD on nanoparticles was successfully characterized by various techniques. The functionalized MSNs with RGD conjugation on the surface showed good cytocompatibility as evidenced by in vitro cell viability assays and cytoskeleton observation. The dual-factor delivery system could quickly release plasmid DNA (pDNA), while releasing DEX in a sustained manner. When cultured with the vector bearing bone morphogenetic protein-2 (BMP-2)pDNA, the transfected bone mesenchymal stem cells (BMSCs)were capable of expressing BMP-2 protein. With the simultaneous delivery of DEX and the BMP-2 gene, this dual-factor delivery system could significantly enhance the level of osteogenic differentiation of BMSCs, as demonstrated by in vitro results of alkaline phosphatase (ALP)activity, expression of osteo-related genes, and calcium deposition. Therefore, the versatile functionalized MSNs nanocarrier for codelivery of osteogenic gene and drug may be considered as a promising dual-delivery system to synergistically enhance the osteogenic outcomes of stem cells.
Keywords: MESOPOROUS SILICA NANOPARTICLES; COPOLYMER; DUAL-FACTOR; SIMULTANEOUS DELIVERY; OSTEOGENIC DIFFERENTIATION